2019
DOI: 10.5937/mp70-22182
|View full text |Cite
|
Sign up to set email alerts
|

Nonsuicidal self-injury among adolescents with disorders of emotion and behavior: Clinical characteristics and association with suicidality

Abstract: Introduction: Nonsuicidal self-injury (NSSI) is defined as a separate entity in the fifth version of the Diagnostic and Statistical Manual of Mental Disorders (DSM-V) as a "condition for further study". Although the NSSI is not driven by suicidal intention, studies do show its association with suicidal phenomena, but this relationship is still unclear. Aim: The aim of this paper was to examine the characteristics of the NSSI phenomenon among adolescents with disorders of emotion and behavior, with special emph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(35 reference statements)
2
0
0
Order By: Relevance
“…Our research also confirmed earlier findings of greater frequency of NSSI in females that is particularly significant in a clinical sample of adolescents 8,14,22,23 . One of the explanations for this could be that male adolescents rarely look for help regarding their psychological difficulties due to fear of stigmatization.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our research also confirmed earlier findings of greater frequency of NSSI in females that is particularly significant in a clinical sample of adolescents 8,14,22,23 . One of the explanations for this could be that male adolescents rarely look for help regarding their psychological difficulties due to fear of stigmatization.…”
Section: Discussionsupporting
confidence: 91%
“…More than half of the participants in our clinical sample (52.3%) had NSSI at least once in the last year. These findings have been confirmed in previous research studies indicating that the frequency of NSSI in the clinical population goes up to 60% 7,21,22,23 . Results of the current study are in line with the Kaess et al 24 research finding who found that the frequency of NSSI in a clinical sample with one NSSI is 60% and 50% for repetitive NSSI.…”
Section: Discussionsupporting
confidence: 88%